Diversity, composition, and structure of a highly endangered habitat: the seasonally dry forests of Tarapoto, Peru - García-Villacorta, Roosevelt (2009)
Between March and April 2006, I studied ten localities with seasonally dry forests located along the Tarapoto- Juanjui road, San Martin. At each site ten 50×2 m transects totalling 1000 m² (0,1 ha) were laid out along a 180 m baseline where all standing trees with diameter at breast height (DBH) greater than 2,5 cm were measured, counted and identified to species. I found a total of 146 species and 2814 individuals with DBH ≥ 2,5 cm. Within the study area, Myrtaceae was the most species rich family with 14 species followed closely by Leguminosae with 12 species. Annonaceae and Myrtaceae had the highest number of individuals (461 and 412, respectively), whereas Sapotaceae, with only 160 stems, had the highest basal area. The latter was mainly due to Manilkara bidentata (A. DC.) A. Chev. (“Quinilla”), the most important tree species in the seasonally dry forests of Tarapoto. Two species were present at all sites: Coccoloba sp. 1 (Polygonaceae) and Oxandra espintana (Spruce ex Benth.) (Annonaceae), whereas 53 species occurred only at one site. The seasonally dry forests of Tarapoto have an intermediate diversity compared to the other dry forests in the Neotropics and similar diversity compared to the Peruvian dry forests of the Pacific coast. Most of the tree community in these forests belong to geographically widespread species compared to shrubs that are mostly restricted to dry forests habitats. The areas located near the Tarapoto-Juanjui road (“carretera marginal”) have the most disturbed forests. The best representations of Tarapoto’s seasonally dry forests are located west and south of the locality of Picota, in the Area de Conservación Municipal “El Quinillal”, and in the Bombonajillo and Ponasillo basins. These results highlight the pressing needs for conservation efforts in the area, before these unique forests are forever lost due to the continuing expansion of agricultural fields and logging activities prevalent in the region.